Desarrollo de la nueva versión de la aplicación móvil con módulo de administración web para la transmisión de la UTC RADIO 102.9 fm en dispositivos android. - Alquinga Chasipanta, Byron Esteban (2020)
This technological proposal consists of developing the new version of the mobile application with a web management module for the UTC Radio 102.9 FM. This application allows the transmission of the content produced by the radio through streaming. These contents are live programs, interviews, news, and relevant information published by the radio to inform the community. For the development of the project, field research was carried out using observation and interview techniques, which helped define the system's requirements. For the design, the Unified Modeling Language (UML) was used and, in general, for the whole development, the Iterative-Incremental Model to divide the problem in a set of tasks grouped in small repetitive stages that were used both for the development of the mobile application and for the web administration module. All the tools used are Open Source, the Java programming language oriented to multiplatform objects, the integrated development environment (IDE) Android Studio, the programming language PHP, and the database manager MySQL; in this way, the objective is achieved; currently, the application is deployed, downloadable in the Play Store with the name: UTC Radio 102.9 FM.